From Policy to Practice: What Explains the Gaps in Voter List Accuracy in Indonesia’s Dispersed Island Districts? - Hamzah, Baharudin; Liliweri, Aloysius; Sayrani, Laurensius Petrus; Rohi, Rudi (Journal Public Policy, 2025)
This study examines the persistent gap between centralized voter registration policy and its local implementation in Indonesia’s geographically dispersed island districts, focusing on Flores Timur in East Nusa Tenggara Province. The aim is to understand why voter registration inaccuracies undermine democratic inclusion despite institutional reforms and digital innovations. Using a qualitative case study approach, the research draws on 28 in-depth interviews with electoral officials, civil registry personnel, and community stakeholders, complemented by document analysis. The findings reveal three interrelated problems: institutional fragmentation between the General Election Commission (KPU) and the Civil Registry Office (Disdukcapil); lack of real-time interoperability between the Sidalih and e-KTP data systems; and procedural redundancies due to multi-level manual validations. These challenges result in the persistent exclusion of eligible voters, particularly in remote and marginalized communities. Moreover, the study documents how local actors respond through informal workarounds, such as using village records and social networks, which further entrench inequality and data inconsistency. As a key theoretical contribution, this article introduces the concept of data governance dissonance to explain how institutional and technological misalignment perpetuates electoral exclusion in decentralized and resource-constrained democracies. The study provides insights for improving voter registration systems in fragmented governance settings globally.